THE ROLE OF AUDIT COMMITTEE EFFECTIVENESS IN ENHANCING TIMELINESS OF CORPORATE FINANCIAL REPORTING IN THE NIGERIAN INSURANCE INDUSTRY - Alabi, Abdulkadri; Sanni, Mubaraq; Abdulrasaq, Mustapha (Accounting Profession Journal (APAJI), 2022)
This study investigated the impact of audit committee effectiveness on financial reporting timeliness in the Nigerian insurance industry. The study employed secondary data for the years 2012 - 2020. Hypotheses were tested using the Ordinary Least Square (OLS) method. The results revealed a significant relationship between timely financial reporting and audit committee size, expertise, and diligence. There was a negative but insignificant association between audit committee independence and financial reporting. The study concluded and recommended that audit committee effectiveness affects financial reporting timeliness in the insurance industry and that firms should increase the size and meeting frequency of the committee.